The pillars of the earth - Follett, Ken. (New York : New American Library, 2007)
Set in twelfth-century England, this epic of kings and peasants juxtaposes the building of a magnificent church with the violence and treachery that often characterized the Middle Ages.
Originally published: New York : Morrow, 1989. With added pref.
"Oprah's book club"--Cover.
Keywords: Great Britain -- History -- Stephen, 1135-1154 -- Fiction